2012
DOI: 10.1063/1.4740231
|View full text |Cite
|
Sign up to set email alerts
|

High throughput fabrication of disposable nanofluidic lab-on-chip devices for single molecule studies

Abstract: An easy method is introduced allowing fast polydimethylsiloxane (PDMS) replication of nanofluidic lab-on-chip devices using accurately fabricated molds featuring cross-sections down to 60 nm. A high quality master is obtained through proton beam writing and UV lithography. This master can be used more than 200 times to replicate nanofluidic devices capable of handling single DNA molecules. This method allows to fabricate nanofluidic devices through simple PDMS casting. The extensions of YOYO-1 stained bacterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 52 publications
(50 reference statements)
0
40
0
Order By: Relevance
“…PDMS microdevices, for instance, cannot be fabricated in a highthroughput manner, because master molds are mechanically unstable and therefore the process is inadequate for industrial applications (van Kan et al, 2012). Furthermore, the disadvantages of PDMS (e.g., hydrophobicity, absorption of molecules toxicity of monomers, and vapor permeability) outweigh the advantages frequently reported in the literature (e.g., easy fabrication, gas permeability, and optical transparency).…”
Section: Fabrication Methods and Materials Of Cell Chip Systemsmentioning
confidence: 94%
“…PDMS microdevices, for instance, cannot be fabricated in a highthroughput manner, because master molds are mechanically unstable and therefore the process is inadequate for industrial applications (van Kan et al, 2012). Furthermore, the disadvantages of PDMS (e.g., hydrophobicity, absorption of molecules toxicity of monomers, and vapor permeability) outweigh the advantages frequently reported in the literature (e.g., easy fabrication, gas permeability, and optical transparency).…”
Section: Fabrication Methods and Materials Of Cell Chip Systemsmentioning
confidence: 94%
“…1,2 Nowadays, nanofluidics has become a fundamental and critical technique to study nano-scale fluidic, molecular, and ion properties due to the special phenomena that only occur in nanochannels. 1,3,4 In recent years, a substantial amount of research on nanofluidic chips has been reported, such as protein analysis, 5-7 DNA stretching, 8,9 virus characterization, 10 and ion separation. [11][12][13] Different Si/silica nanofluidic chips have been fabricated by using reactive ion etching, 14,15 electron beam, 16 focused ion beam, 17,18 and proton beam technique.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays nanofluidic has become a fundamental and critical technique to study nano-scale fluidic, molecular and ion properties due to the special phenomena only occur in nanochannels (Sparreboom et al 2009;Freedman et al 2013). In recent 5 years, a substantial amount of research has been reported such as protein analysis (Chun et al 2013;Sang et al 2013), DNA stretching (van Kan et al 2012;Pedersen et al 2013), virus characterization (Zhou et al 2011) and ion separation (Tsukahara 2010;Gillespie and Pennathur 2013) based on nanofluidic chips.…”
Section: Introductionmentioning
confidence: 99%
“…For the fabrication of nanofluidic chips, there are some methods can be used: (1) Beam based method, such as proton beam (PB) (van Kan et al 2012), electron beam (EB) (Yasui et al 2011), and focused ion beam (FIB) (Menard and Ramsey 2011). To fabricate nanofluidic chips, microchannels should also be fabricated.…”
Section: Introductionmentioning
confidence: 99%